Investigating the effects of smartboard on EFL learners’motivation and vocabulary achievement at a Saudi university - Ahmad, Waqar (2020)
Smartboards are getting increasingly popular in the field of English language teaching and learning. The Smartboard is an effective tool for conducive teaching and learning English that has turned the traditional environments of the classrooms to be more interesting and encouraging. Smartboards are now widely used in the teaching and learning process all over the world and also in Saudi Arabia. Literature reviews suggest that Saudi students usually lack motivation for studying English as a foreign language. This study plans to investigate the impact of Smartboard on EFL learners’ vocabulary achievement and motivation at a Saudi university. The study involves 123 students enrolled in a Preparatory Year Program at a public sector Saudi university. The objective of the study is to examine the effects of Smartboard on EFL learners’ motivation. The study also aims to identify the EFL learners’ vocabulary achievement when learning English with the help of Smartboard in the classroom. The study employed a quasiexperimental design, whereby intact group of students were used. Four (4) intact groups were selected, in which two (2) of the groups were termed as experimental groups and the other two (2) as control groups. The experimental group students were taught using the Smartboard while the control group students were taught with the traditional whiteboard, pen and book method. The treatment was given for six (6) weeks. Vocabulary achievement test, and two (2) questionnaires (A & B) were used to collect quantitative data whereas semi-structured interviews were used to collect qualitative data. The quantitative data were analyzed using the Statistical Package for Social Sciences (SPSS) v21 software, whereas the qualitative data were analyzed with MAXQDA 2018 software. While examining the results of the vocabulary achievement test, it was found that the experimental group learners in their vocabulary achievement test attained a higher mean score than the control group learners’ mean score. Independent samples t-test was used to measure the difference between the two groups and it was found that there is a significant difference at (α = 0.05) in the total mean score of the post-test between the experimental and control group, in favour of the experimental group, who learned via the Smart Board. Correspondingly, one-way ANOVA was utilized to evaluate and compare the mean score of the experimental and control group on their post-treatment survey results, and the difference between the two (2) groups was found to be significant at 0.05 level. Thus, the results of Questionnaire A revealed that the subjects of the experimental group are enthusiastic and motivated as compared to the control group students. Results of Questionnaire B exhibits that the overall positive responses rate is 75.31%, which indicated that the vast majority of the participants agreed to the statements. Moreover, the data yielded from the participants’ interviews revealed nearly all the subjects of the experimental group considers Smartboard to be a significant addition to their academic life and the advantages they have attained with the help of Smartboard are countless. Thus, the use of the Smartboard in the Saudi EFL classrooms has been found to be helpful to provide comprehensible input in low filter environment. The results of the study therefore, ascertained that the Smartboard enhanced the participation and involvement of the Saudi EFL learners in their English classes.